2020
DOI: 10.1177/0734016820981629
|View full text |Cite
|
Sign up to set email alerts
|

Championing Change to Save Lives: A Call to Action to Implement Reforms to Increase Use of Medications to Treat Opioid Use Disorder in Correctional Settings

Abstract: The disproportional rates of opioid use disorder (OUD) in U.S. correctional facilities make them prime intervention points to treat OUD utilizing medication to treat opioid use disorder (MOUD), the evidence-based clinical standard of care. MOUD has been shown to be effective to support recovery and reduce recurrence of OUD, overdose deaths, and recidivism for justice-involved persons both while incarcerated and once they reenter their communities. Despite the high prevalence, most jails and prisons do not offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Furthermore, participants indicated that a lack of clarity around their impending release details contributed to anxiety and an inability to adequately plan for OAT care and general reintegration. These observations underscore the need for timely, consistent, and collaborative community release planning and case management that takes personal readiness/motivation and key determinants of release outcomes into consideration towards setting individuals up for improved community reintegration and success [ 120 ]. Participants also expressed that an important facilitator to successful community reintegration was familial support; meanwhile, they indicated a main barrier would be returning to places where their families reside, possibly increasing the risks of exposure to deviant social networks and re-accessing or relapsing to substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants indicated that a lack of clarity around their impending release details contributed to anxiety and an inability to adequately plan for OAT care and general reintegration. These observations underscore the need for timely, consistent, and collaborative community release planning and case management that takes personal readiness/motivation and key determinants of release outcomes into consideration towards setting individuals up for improved community reintegration and success [ 120 ]. Participants also expressed that an important facilitator to successful community reintegration was familial support; meanwhile, they indicated a main barrier would be returning to places where their families reside, possibly increasing the risks of exposure to deviant social networks and re-accessing or relapsing to substance use.…”
Section: Discussionmentioning
confidence: 99%